IMMUNOPATHOGENESIS OF DENGUE SHOCK SYNDROME - Karta Sawenda; I Wayan Putu Sutirta Yasa; DAP Rasmika Dewi; Bagus Komang Satriyasa (Faculty of Medicine, Udayana University, 2013)
Dengue is the most important emerging tropical viral disease of humans in the world today. It is estimated that there are between 50 and 100 million cases of dengue fever (DF) and about 500.000 cases of dengue haemorrhagic fever (DHF) each year which require hospitalization. Persons of all ages can be infected and develop dengue fever. However, children younger than 15 years typically present with only a nonspecific self-limited febrile illness. Untreated dengue hemorrhagic fever mostly likely progresses to dengue shock syndrome which is defined as dengue fever with signs of circulatory failure. The prognosis depends on prevention or early recognition and treatment with case fatality rate is as high as 12% to 14% once shock has set in. Management of dengue fever requires rest, oral fluids to compensate for losses via diarrhoea or vomiting, antipyretics and analgesics. Patients who present with shock may require central venous pressure monitoring. An arterial line may be required in unstable patients for the assessment of blood gases, electrolytes, and coagulation profile to help identify patients needing ventilatory support.